Exploring the Phenomenon of Timelessness in Morocco: Insights from Paul Bowles and Other Travel Writers - Mohamed El Mehdi Jouay; K. El Fouadi (European Scientific Journal, ESJ, 2024)
This article aims to explore the phenomenon of timelessness in Morocco through the insights of renowned travel writers such as Paul Bowles. The semi-systematic method was used primarily due to the limited amount of research done on the topic of timelessness. It will analyze the representations of Morocco in Western discourse, particularly in the context of Western Orientalism. Thanks to decolonization, deconstructionism, and Edward Said’s Orientalism, hitherto neglected travel writing has elicited academic responses from scholars who have recognized that travel writing is not simply an innocent and objective description of a traveler’s encounters in a foreign land. Instead, it is a genre that is inherently political, intertwined with projects of orientalism, colonialism, imperialism, and post-colonialism, and characterized by a hegemonic gaze directed towards the other, often marginalizing the voices of peripheral people. This research references books, notable authors, and Western explorers who commonly mention the unchanging quality of time in the Orient, particularly in Morocco. Additionally, the study will draw on the insights of Edward Said to explain why this timelessness was prevalent in the 20th century.